Natural variability in the disease course of SSc-ILD: implications for treatment - Vonk, Madelon C.; Walker, Ulrich A.; Volkmann, Elizabeth R.; Kreuter, Michael; Johnson, Sindhu R.; Allanore, Yannick (European respiratory review, 2021)
Interstitial lung disease (ILD) affects approximately 50% of patients with systemic sclerosis (SSc) and is the leading cause of death in SSc. Our objective was to gain insight into the progression of SSc-associated ILD (SSc-ILD). Using data from longitudinal clinical trials and observational studies, we assessed definitions and patterns of progression, risk factors for progression, and implications for treatment. SSc-ILD progression was commonly defined as exceeding specific thresholds of lung function worsening and/or increasing radiographic involvement. One definition used in several studies is decline in forced vital capacity (FVC) of ≥10%, or ≥5-10% plus a decline in diffusing capacity of the lung for carbon monoxide ≥15%. Based on these criteria, 20-30% of patients in observational cohorts develop progressive ILD, starting early in the disease course and progressing at a highly variable rate. Risk factors such as age, FVC, extent of fibrosis and presence of anti-topoisomerase I antibodies can help predict progression of SSc-ILD, though composite risk scores may offer greater predictive power. Whilst the variability of the disease course in SSc-ILD makes risk stratification of patients challenging, the decision to initiate, change or stop treatment should be based on a combination of the current disease state and the speed of progression.
Gesehen am 09.07.2021